Optimasi Formula Lotion Ekstrak Etanol Bunga Krisan (Crhysanthemum cinerariaefolium (Trevir.)Vis.) menggunakan Kombinasi Asam Stearat dan Setil Alkohol sebagai Repelan dengan Metode Simplex Lattice Design - Rifkarosita Putri Ginaris; Rina Herowati; TN Saifullah Sulaiman (Jurnal Farmasi Indonesia, 2022)
Chrysanthemum flower (Crhysanthemum cinerariaefolium (Trevir.) Vis.) contains flavonoids, saponins and polyphenols which are efficacious as repellents against Aedes aegypti mosquitoes. Lotions with a combination of stearic acid and cetyl alcohol are used to improve adhesion and thickening. The purpose of this study was to make a lotion preparation using a combination of stearic acid and cetyl alcohol to obtain optimum physical quality and obtain an effective concentration of chrysanthemum flower extract as a repellant lotion against A. aegypti mosquitoes and a safe effect on the skin. Chrysanthemum extraction was carried out using 70% ethanol. Chrysanthemum ethanol extract was then dose oriented with a concentration of 1.2%. Chrysanthemum flower ethanol extract lotion formulations were made into 7 formulations using stearic acid and stearic acid bases, Formula I 9.00: 8.00%, Formula II 15.00: 2.00%, Formula III 11.00: 6.00 %, Formula IV 15.00: 2.00%, Formula V 13.00: 4.00%, Formula VI 7.00: 10.00%, Formula VII 11.00: 6.00%. Determination of the optimum formula using the Simplex Lattice Design method using the Design Expert program. The optimum formula is obtained, then tested for physical stability including viscosity, adhesion, dispersion and pH. Physical stability was tested using the One Way Anova method followed by Tuckey HSD. Irritation test with the method of Human 4-hour patch test and hedonic test by giving questions to probandus. Chrysanthemum extract concentration of 1.2% has pharmacological activity that functions as a repellent power of mosquitoes. The optimum combination of stearic acid and cetyl alcohol, 7% stearic acid and 10% cetyl alcohol, get optimum physical quality with the Simplex Lattice Design method. The optimum formula of chrysanthemum flower ethanol extract lotion does not have good physical quality stability based on the parameters of adhesion, dispersion, pH and viscosity during 30-day storage. The lotion irritation test results obtained an irritation index of 0, so it can be concluded that the optimum formula of chrysanthemum extract lotion extract does not cause skin irritation and is quite acceptable to probandus.